Disparities in physical activity descriptive norms: the case of immigrants and racial/ethnic minorities in New York City. Issue 5 (3rd September 2021) - Sano, Yujiro; Antabe, Roger; Kwon, Eugena; Atuoye, Kilian Nasung; Anfaara, Florence Wullo; Luginaah, Isaac
ABSTRACT: Descriptive norms – conceptualized as the tendency for individuals to initiate given behaviours because significant others are engaged – have been considered helpful in increasing the uptake of physical activity. Yet, the literature pays little attention to the attainment of descriptive norms among the populations with inadequate levels of physical activity such as racial/ethnic minorities and immigrants. Using a representative survey from New York City, this study aimed to address this void. We found at the bivariate level that immigrants and racial/ethnic minorities (i.e., Black, Hispanic, and Asian) had lower levels of descriptive norms than their native-born and White counterparts. Importantly, such disparities were completely attenuated once socioeconomic status was controlled for, except for Asian Americans. Based on these findings, we provided some policy implications. First, intervention programs may need to prioritize the integration of minority populations. Second, there is the urgent need to create avenues for the social mixing of immigrants and racial/ethnic minorities, which may provide them opportunities to interact and network with those who actively engage in physical activity. Finally, it is important to reduce socioeconomic disparities between foreign-born and native-born populations as well as racial/ethnic minorities and their white counterparts.